A Review on Real-Time 3D Reconstruction Methods in Dynamic Scene (International Journal of Innovative Computing, 2021)
Advancements made in consumer and readily available RGB-D capturing devices have sparked researcher interest in 3D reconstruction, particularly in dynamic scenes, as well as the quality performance and its speed. The recent advancement in such devices supports the developments of various applications such as teleportation, gaming, volumetric video, and CG films. Real-time 3D reconstruction methods review in a dynamic scene of virtual environment is depicted in this paper. This provides an insight view on how real-time 3D reconstruction beneficial achievement further enables reconstruction systems to be managed in real-time technology such as virtual reality or augmented reality application.
Keywords: 3D Reconstruction, 3D Reconstruction Methods, Dynamic Scenes, Real-time 3D Reconstruction